Canver (canva-animaker): Pengembangan media pembelajaran interaktif pada materi statistika - Tasya Khoerunnisa; Heris Hendriana; linda linda (IKIP Siliwangi, 2026)
Canver (Canva-Animaker) is an innovative interactive learning media integrating Canva visual design and Animaker. This study develops this learning media combined with a Problem Based Learning (PBL) approach to improve students’ mathematical problem-solving abilities in statistics. The aim of this study is to produce interactive learning media that meets validity, practicality, and effectiveness criteria. The research method used is the ADDIE model. The study involved 25 eighth-grade students at a junior high school in Cimahi. The instruments included expert validation sheets, student responsse questionnaires, interview guides, documentation, and problem-solving ability tests. The results indicate that the media is highly valid, with average validation scores of 89.58% (media) and 89.74% (material). Practicality is shown by student responsses with an average score of 89.74%, categorized as very practical. The media is also effective in improving students’ problem-solving abilities, with an N-Gain score of 0.77 (high category). The t-test shows a significant difference between pretest and posttest scores (p < 0.05). Thus, Canva-Animaker media with a PBL approach is an innovative alternative for mathematics learning.